Pendidikan Kaum Tertindas: Perjumpaan Gagasan Pendidikan Paulo Freire dan Ki Hadjar Dewantara dan Harapan Bagi Pendidikan Di Indonesia - Paulus Roby Erlianto; Santo . (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2022)
The true education is education that is capable of humanizing humans beings. It will also continue to be an effective means to educate the nation's life in accordance with the objectives of the Indonesian state. However, in reality, this goal has not been achieved until now. The reality of oppression through the world of education is still happened now. we can see it in government policies on education, such as: the problem concerns the issue quality of education, equity of educational and management of education. First, this obscure direction of education is very visible from the national curriculum of education which is always changing which is not only aimed at improving the quality of education, but also full of ideology, politic, economic interests. Second, the problem of equity of education, which is related to the condition of Indonesian children who cannot get good quality education. Third, management of education issues include government policies, bureaucracy and transparency of education. The ideological and capitalistic situations in education like this has become a field criticized by Paulo Freire and Ki Hadjar Dewantara. These two figures see that human beings must reach their humanity. In other words, they must be free: free from injustice, oppression and even duping. These two figures outline the philosophical ideas of education based on knowledge and life experiences that come into contact with oppression, human suffering both those they experience themselves and those around them. Some parts of their educational views can be recommended in the educational context in Indonesia.